2015
DOI: 10.5152/tpd.2014.3406
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Malaria with Uveitis, Hyperglisemia, and Rasha in a Turkish Radiologist Who Went to Africa

Abstract: ÖZETSıtma başta Sahra altı Afrika olmak üzere dünyada önemli bir sağlık problemidir. Türkiye'de en çok görülen sıtma türü Plasmodium vivax olup başlıca Güneydoğu Anadolu ve Çukurova bölgesinde endemiktir. Globalleşme ve turizme bağlı olarak seyahat ilişkili Plasmodium falciparum olgularında artış gözlenmektedir. Optimal antimalaryal tedaviye rağmen P. falciparum yüksek mortalite ile seyredebilmektedir. Burada mesleki nedenle Afrika'ya giden ve üveit, hiperglisemi ve purpurik döküntünün eşlik ettiği sıtma ile d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…1 When the data from Turkey were investigated, it was found that although local cases of malaria have decreased over the years, important malaria cases have been observed. [11][12][13][14] When signet ring forms are observed within erythrocytes in peripheral smears in the presence of an epidemiological history and periodic high fever, malaria could be considered as the primary diagnosis. 15,16 In the present case, malaria was assumed to be the initial diagnosis, since the ring-shaped parasites were observed within the erythrocytes in the first evaluation, and the region around Turkey is not endemic for human babesiosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 When the data from Turkey were investigated, it was found that although local cases of malaria have decreased over the years, important malaria cases have been observed. [11][12][13][14] When signet ring forms are observed within erythrocytes in peripheral smears in the presence of an epidemiological history and periodic high fever, malaria could be considered as the primary diagnosis. 15,16 In the present case, malaria was assumed to be the initial diagnosis, since the ring-shaped parasites were observed within the erythrocytes in the first evaluation, and the region around Turkey is not endemic for human babesiosis.…”
Section: Discussionmentioning
confidence: 99%
“…İşçi olarak beş yıldır arada Kongo'ya seyahat eden hastanın son olarak üç ay Kongo'da kalma hikayesi vardı. Türkiye'ye gelmeden 10 gün önce sıtma nedeniyle beş gün te- Tedavi bilgisi içeren çalışmalarda 14 P.falciparum sıtması olgusundan yedisinde artemisin, kalan altısında kinin içeren tedavi verildiği bildirilmektedir (5,(9)(10)(11). Bunun yanında Sudan'dan gelen bir işçide gelişen P. falciparum sıtması olgusunun klorokin ile tedavi edildiği bildirilmiştir.…”
Section: Olguunclassified